Description framework of makerspaces: Examining the relationship between spatial arrangement and diverse user populations. (1st March 2023) - Melo, Marijel; March, Laura; Hirsh, Kimberly; Arnsberg, Emily
Abstract: As makerspaces continue to proliferate in academic and public libraries, researchers and educators are increasingly concerned with ensuring these STEM‐rich learning environments are inclusive to historically marginalized student communities. This article offers a new framework, the Description Framework of Makerspaces, to outline the relationship between the spatial qualities of makerspaces and the user population it attracts. This study represents the first phase of a 5‐year research program dedicated to analyzing the everyday life information seeking practices that students (un)intentionally make when deciding to engage with a STEMrich learning environment such as a makerspace. Using constructivist grounded framework to analyze interview data from 17 academic makerspace leaders, we theorize 2 propositions from the main findings: (a) the act of defining a makerspace is difficult and in tension with several imaginings of a makerspace: imagined, ideal, and experienced and (b) a makerspace is significantly composed of affective features that are often unarticulated and abstract. By conceptualizing makerspaces as environments that are configured by both physical and affective characteristics, we reveal insights regarding a baseline conceptualization of the features of a conventional academic makerspace and the design decisions that makerspace leaders make and are confronted with.